2021
DOI: 10.1001/jamaneurol.2020.3406
|View full text |Cite
|
Sign up to set email alerts
|

Disparities Across Sexual Orientation in Migraine Among US Adults

Abstract: Migraine affects 1 in 6 adults and represents the fifth leading cause of emergency department visits in the US. 1 Despite an increasing recognition of disparities in migraine prevalence by race/ethnicity, sex, and socioeconomic status, 1 there is a paucity of research on disparities by sexual orientation. Sexual minority groups (eg, lesbian, gay, bisexual, and other nonheterosexual people) may experience unique discrimination, stigma, and barriers to health care access, thus leading to disparities in physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…To our knowledge, there are no intersectional analyses of episodic migraine [ 116 ]. Prior studies have found disparate rates of self-reported migraine based on race/ethnicity [ 117 ], socioeconomic status [ 116 ], and sexual orientation [ 118 ]. In addition, factors including income, health insurance status, and gender influence access to adequate headache management [ 119 ].…”
Section: Part 2 – Practical Considerations For Sex and Gender Issues ...mentioning
confidence: 99%
“…To our knowledge, there are no intersectional analyses of episodic migraine [ 116 ]. Prior studies have found disparate rates of self-reported migraine based on race/ethnicity [ 117 ], socioeconomic status [ 116 ], and sexual orientation [ 118 ]. In addition, factors including income, health insurance status, and gender influence access to adequate headache management [ 119 ].…”
Section: Part 2 – Practical Considerations For Sex and Gender Issues ...mentioning
confidence: 99%
“…For instance, this pivotal study did not collect data on participants’ sexual orientation or diverse gender identities beyond biological sex, making it impossible to draw any meaningful conclusions about the unique experiences of SGM individuals with migraine. This limitation is particularly important given emerging evidence suggesting that SGM individuals may experience a greater burden of migraine than their cis‐heterosexual peers 2,5 . By not identifying SGM individuals, the American Migraine Prevalence and Prevention Study failed to capture important information about prevalence, predictors, and pain management strategies related to migraine in this key demographic.…”
Section: Lack Of Sgm Representation In Epidemiological Studies Of Mig...mentioning
confidence: 99%
“…According to a recent study by Nagata et al, 2 sexual minorities (i.e., lesbian, gay, and bisexual people) have a 58% greater adjusted odds of migraine compared to those who identify as "exclusively heterosexual" 2 ; however, sexual minorities are not represented in the published statistics from existing large-scale epidemiological studies on migraine. 3 Gender minorities (e.g., transgender and non-binary individuals) are also not represented in this research.…”
Section: Dis Paritie S In Mig R Aine Among S E Xual and G Ender Minor...mentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Migraine is associated with a number of comorbidities, including higher rates of ischemic stroke, gastrointestinal disorders, and psychiatric disorders, which can contribute to further disability. 2 , 3 Studies suggest greater odds of migraine in presumably cisgender lesbian women, cisgender gay men, and bisexual people of any gender 4 , 5 ; however, little is known about migraine prevalence and severity in transgender and gender nonbinary individuals. Risk factors for migraine-associated disability in sexual and/or gender minority (SGM) individuals (an inclusive term used to describe individuals whose sexual orientation and/or gender identity do not align with societal expectations based on their birth-assigned sex, including, but not limited to, those who identify as lesbian, gay, bisexual, transgender, and queer) are also unknown.…”
mentioning
confidence: 99%